2010
DOI: 10.1007/s00246-010-9809-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Studies and Radiofrequency Catheter Ablation of Ectopic Atrial Tachycardia in Children

Abstract: Ectopic atrial tachycardia (EAT) often resists medical therapy, making radiofrequency catheter ablation (RFCA) the preferred treatment. This study reviewed the records of 35 patients who underwent electrophysiologic studies (EPS) and 39 RFCA procedures for EAT during a 10-year period. Of the 35 patients, 10 (28%) presented with decreased ventricular function and tachycardia-induced cardiomyopathy (TIC). The EAT originated on the right atrial side in 19 patients (54%) and on the left atrial side in the remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 18 publications
3
29
0
1
Order By: Relevance
“…Cummings et al showed improved acute ablation success rates with a lower incidence of recurrence using 3D electroanatomic mapping compared to 2D mapping techniques in their patients undergoing RF ablation procedures for pediatric AT . Similarly, Toyohara et al reported acute success in all of their pediatric AT patients (35/35) and 11% recurrence undergoing RF ablation using 3D mapping system . In a recent study, Dieks et al reported acute success in 14 of 16 patients (87.5%) using modern mapping systems .…”
Section: Discussionmentioning
confidence: 99%
“…Cummings et al showed improved acute ablation success rates with a lower incidence of recurrence using 3D electroanatomic mapping compared to 2D mapping techniques in their patients undergoing RF ablation procedures for pediatric AT . Similarly, Toyohara et al reported acute success in all of their pediatric AT patients (35/35) and 11% recurrence undergoing RF ablation using 3D mapping system . In a recent study, Dieks et al reported acute success in 14 of 16 patients (87.5%) using modern mapping systems .…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, children with FAT refractory to initial treatments undergo a complex clinical course involving multiple medications and catheter procedures. With emerging experience to show that catheter therapies are safe and effective, even in young patients, 21 family choice is often the key determinant for using medical versus ablation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Toyohara et al 21 reported a series of 35 pediatric FAT patients who had 100% acute success and 11% recurrence with RFA using the CARTO Navigation System (Biosense Webster, Inc, Diamond Bar, CA). Data from Cummings et al 13 showed improved ablation success and recurrence rates with electroanatomic mapping compared with conventional mapping for pediatric FAT.…”
Section: Discussionmentioning
confidence: 99%
“…Catheter ablation was effective in 81% of patients in whom it was used. The use of electroanatomical mapping for ablation improved success (102) and decreased recurrence (103). …”
Section: Aic In Childrenmentioning
confidence: 99%